Export processing zones and the composition of greenfield FDI - Ronald B. Davies; Rodolphe Desbordes (University College Dublin, UCD School of Economics, 2018)
Export processing zones (EPZs) are an increasingly common type of special economic zone. They are designed to facilitate international trade by lowering trade costs, such as import duties and/or export taxes. EPZs should thus be particularly attractive locations for multinational enterprises engaging in vertical, trade-intensive, foreign direct investment (FDI). Using data on worldwide greenfield FDI projects over the period 2003-2014, we find patterns consistent with this hypothesis. EPZs have a large positive effect on manufacturing FDI projects with a production focus, especially in trade- and labour-intensive sectors. Overall, our results suggest that EPZs are an effective tool to attract manufacturing FDI which exploit the opportunities offered by global value chains.
Keywords: F23; F13; 330; Export Processing Zone; Special Economic Zone; Greenfield FDI; Global Value Chain